Disnep's ali baba and the 40 thieves (Random House New York, 1979)
Ali Baba, a poor woodcutter, stumbles upon a secret cave filled with treasure, guarded by a band of 40 thieves. Using his wit and courage, he outsmarts the thieves with the help of his clever servant girl, Morgiana. The story is a classic tale of bravery, cunning, and the triumph of good over evil.